2002
DOI: 10.1034/j.1600-051x.2002.291109.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue structure, and IL‐1β, IL‐8, and TNF‐α secretions after contact by engineered human oral mucosa with dentifrices

Abstract: The use of dentifrice is part of an oral prophylaxis that aims at keeping bacteria in check within the dental plaque. When introduced into the oral cavity, dentifrice also comes in close contact with the oral epithelium. Our goal was to evaluate the effects of dentifrices on tissue structure and pro-inflammatory mediator release by epithelial cells. For this purpose, tri-dimensional engineered human oral mucosa (EHOM) was produced using normal human palatal fibroblasts and epithelial cells. EHOMs were either t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…11 Schmalz et al studied mucosal irritancy of metals used in dentistry by introducing these materials onto a three-dimensional fibroblast-keratinocyte co-culture on nylon mesh 12 and also a 3D culture of TR146 cells grown on polycarbonate filters. 13 These in vitro models seem promising for mucotoxicity evaluation of dental biomaterials, since they reflect the clinical situation better than do single-layer cell culture test models.…”
Section: Discussionmentioning
confidence: 99%
“…11 Schmalz et al studied mucosal irritancy of metals used in dentistry by introducing these materials onto a three-dimensional fibroblast-keratinocyte co-culture on nylon mesh 12 and also a 3D culture of TR146 cells grown on polycarbonate filters. 13 These in vitro models seem promising for mucotoxicity evaluation of dental biomaterials, since they reflect the clinical situation better than do single-layer cell culture test models.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the WPI/ DEG biofilm is the most appropriate whey proteinbased biofilm for keratinocyte growth and stratification. It is interesting to underline the very particular behavior of these biofilms being able to allow the keratinocyte proliferation and differentiation in two different layers, comparable to keratinocytes cultured on fibroblastpopulated collagen gels [34,35]. In both models, the keratinocytes proliferated horizontally until the entire surface of the substrate was covered, and then differentiated vertically into basal, supra-basal, and corneous layers.…”
Section: Biofilm Effect On Keratinocytes Proliferation and Stratificamentioning
confidence: 98%
“…buccal or gingival) is seldom despite researchers have shown that the reconstituted organotypic tissues of the oral cavity, e.g. 3D oral mucosal tissues, express differentiated characteristics comparable to the in vivo situation and can be used to study innate immunity and pathobiology of the oral mucosa, including gingivitis, candidiasis, oral cancer and inflammation (Andrian et al, 2004; Ceder et al, 2007; Hansson et al, 2001; Klausner et al, 2007; Mostefaoui et al, 2002; Moyes et al, 2010; Walle et al, 2006; Wang e al., 2001). To our knowledge, this study would be the first to report the effects of CS exposure on oral organotypic tissue models at their air–liquid interface.…”
Section: Introductionmentioning
confidence: 99%